2012
DOI: 10.3109/07357907.2012.707265
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Paclitaxel Resistance in Epithelial Ovarian Carcinoma Cells by a MUC1 Aptamer-let-7i Chimera

Abstract: The purpose of this study was to establish tumor tissue specific delivery of let-7i miRNA to reverse paclitaxel-induced chemoresistance. A chimera that combines MUC1 aptamer and let-7i miRNA was tested in OVCAR-3 ovarian cancer cells. Results demonstrated that the chimera can specifically be delivered into OVCAR-3 cells and the released let-7i significantly sensitized the role of paclitaxel in inhibiting cell proliferation, inducing cell apoptosis, and decreasing long-term cell survival. The chimera achieved r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 18 publications
0
38
1
Order By: Relevance
“…The let-7 isoforms let-7i and miR-98 were shown to decrease expression of PGRMC1 in SKOV-3 ovarian cancer cells in response to P4 treatment [56]. A study by Liu et al fuither supports this idea in which a MUCl aptamer-let7i chime1ic system was used to selectively deliver let7i miRNAs to OVCAR-3 cells [57]. The result was a decrease in PGRMC1 expression and concomitant increase in chemosensitivity to paclitaxel treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The let-7 isoforms let-7i and miR-98 were shown to decrease expression of PGRMC1 in SKOV-3 ovarian cancer cells in response to P4 treatment [56]. A study by Liu et al fuither supports this idea in which a MUCl aptamer-let7i chime1ic system was used to selectively deliver let7i miRNAs to OVCAR-3 cells [57]. The result was a decrease in PGRMC1 expression and concomitant increase in chemosensitivity to paclitaxel treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, miRNA let-7i was the first member of the miRNA family identified to be associated with tumor drug sensitivity, and was observed to play an indirect anti-tumor role by increasing the cell sensitivity to chemotherapeutic drugs (13). Lee et al (14) demonstrated that the expression of let-7i was decreased in platinum-resistant ovarian tumor cells, and downregulation of the expression of let-7i could increase ovarian cancer resistance to cisplatin, suggesting that let-7i could be used as a chemical marker to evaluate the prognosis of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Let-7a, another tumor suppressor miRNA that belongs to let-7 family, has also been proposed as a potential biomarker for determining response to paclitaxel [251]. With the objective of delivering let-7i specifically to OC cells, let-7i was combined with MUC1 aptamer [252]. Once delivered, let-7i was observed to down-regulate cell cycle-associated factors, resulting in reversal of paclitaxel resistance.…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%